2018
DOI: 10.21767/1791-809x.1000572
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Health Service Utilization in Pastoralist Communities of South Omo Zone, Southern Ethiopia

Abstract: Background: Almost all pastoralist communities in Sub-Saharan Africa are living in arid and semi-arid areas and are mobile to search water, grass and suitable place for themselves as well as for their livestock. Their mobility is a strategy to manage efficiently the uncertainty in a fragile environment where settled life is risky. Studies show that mobility renders the utilization of health and other social services rather difficult. Outpatient service utilization pattern in pastoralist communities in Ethiopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Only 10% of pastoralists in Southern Ethiopia make use of modern healthcare facilities in case of illness. The majority seeks aid from traditional healers or prefers self-treatment ( Kawza, Dejene, and Hailemariam 2018 ). Carruth (2014) found in her study that the pastoralists’ perception of illness can be described as pluralistic and ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Only 10% of pastoralists in Southern Ethiopia make use of modern healthcare facilities in case of illness. The majority seeks aid from traditional healers or prefers self-treatment ( Kawza, Dejene, and Hailemariam 2018 ). Carruth (2014) found in her study that the pastoralists’ perception of illness can be described as pluralistic and ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…For pastoralists as a socially and geographically marginalized population, access to biomedical health services is challenging [ 18 , 20 ]. Studies of the proportion of pastoralists in Ethiopia who use health services to treat their illnesses vary widely according to region, distance to health facilities and other factors such as mobility [ 21 23 ]. A study in rural Western Ethiopia found that 36.7% of households reporting illness episodes were self-medicating with modern drugs, most commonly antibiotics and analgesics.…”
Section: Introductionmentioning
confidence: 99%
“…Common reasons among pastoralists for not visiting health facilities are the far distance of health institutions from the place of residence or cultural beliefs that health services lack efficacy for certain health problems [ 21 ]. In addition, the necessary resources especially for treating pain, such as pain medication, are often not available in health care facilities [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation